2020
DOI: 10.1186/s13054-020-03214-9
|View full text |Cite
|
Sign up to set email alerts
|

High-flow nasal cannula oxygen therapy versus non-invasive ventilation for chronic obstructive pulmonary disease patients after extubation: a multicenter, randomized controlled trial

Abstract: Background: High-flow nasal cannula (HFNC) oxygen therapy is being increasingly used to prevent postextubation hypoxemic respiratory failure and reintubation. However, evidence to support the use of HFNC in chronic obstructive pulmonary disease (COPD) patients with hypercapnic respiratory failure after extubation is limited. This study was conducted to test if HFNC is non-inferior to non-invasive ventilation (NIV) in preventing post-extubation treatment failure in COPD patients previously intubated for hyperca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
95
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 30 publications
4
95
0
8
Order By: Relevance
“…In clinical practice, HFNCs are used to manage acute respiratory failure (ARF), prevent hypoxemia during procedures, and prevent postextubation hypoxemia [1][2][3][4][5][6][7]. As almost 20% of patients who undergo planned extubation require reintubation because of hypoxemia, and the HFNC is a useful oxygen delivery modality in this setting, HFNCs are commonly used to prevent reintubation after planned extubation [4,5,[8][9][10][11][12]. As the HFNC can maintain the oxygen concentration despite a patient's declining status, clinicians may be hesitant to reintubate even if the patient's condition deteriorates.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, HFNCs are used to manage acute respiratory failure (ARF), prevent hypoxemia during procedures, and prevent postextubation hypoxemia [1][2][3][4][5][6][7]. As almost 20% of patients who undergo planned extubation require reintubation because of hypoxemia, and the HFNC is a useful oxygen delivery modality in this setting, HFNCs are commonly used to prevent reintubation after planned extubation [4,5,[8][9][10][11][12]. As the HFNC can maintain the oxygen concentration despite a patient's declining status, clinicians may be hesitant to reintubate even if the patient's condition deteriorates.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically HFO had advantages over NIV as decreased risk of adverse effects like mouth dryness, leaks and pressure sores, easier clearance of secretions, and enhanced patient comfort [19] . Tan et al [23] emphasized this advantage with better tolerance and higher comfort than NIV besides similar WF among COPD patients after extubation. We did not investigate this aspect while the need for NIV or HFO more than 48 hours later was higher in the NIV group (72% vs 9.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous physiological studies have illustrated that high-flow airflow can wash the nasopharyngeal dead space and produce a low level of 3-6 cmH 2 O positive endexpiratory pressure [14][15][16], which is the theoretical basis for HFNC in the treatment of mild hypercapnia. A few studies have suggested that HFNC can replace NIV for patients with hypercapnia [17,18], while it is generally not applicable to severe type 2 respiratory failure. However, the small sample sizes in these studies have left the specific indications for HFNC in the treatment of hypercapnia unclear.…”
Section: Discussionmentioning
confidence: 99%